Disasters and biodiversity: case study on the endangered endemic marine ornamental Banggai cardinalfish. (April 2019) - Moore, A M; Ndobe, S; Yasir, I; Jompa, J
Abstract: Disasters are notoriously unpredictable; they can strike anytime, anywhere. However, in this Anthropocene Epoch, humanity has increased the likelihood of many disasters, as well as their likely severity and socio-ecological impacts, with implications for the future of natural resources; in particular, marine ecosystems and biodiversity, and the human communities who rely on them. This case study focussed on the Banggai cardinalfish ( Pterapogon kauderni ), a unique species of global conservation concern, and its native habitat in the Banggai Archipelago, at the centre of the Coral Triangle (CT) global marine biodiversity hotspot. To evaluate future risks and implications, we looked back to the past, including an overview of what is known regarding the origins and evolution of this species and its habitat, as well as past natural disasters in the Banggai Archipelago, Central Sulawesi, Indonesia. We then reviewed current status and trends affecting the likelihood of exposure and the vulnerability of endemic P . kauderni populations and habitat, overall and at the evolutionary significant unit (ESU) scale, to disasters caused by tectonic phenomena, disasters related to weather and anthropogenic climate change (e.g. mass coral bleaching, sea level rise), and the synergies between disaster impacts and localised human activities. Finally, we considered management options with potential for mitigating disaster risk and increasing resilience, with benefits for both biodiversity and human welfare, as well as avenues for future research. We conclude that local action can buy time, but it is likely that the eventual fate of this "flagship" species, as well as the human communities of this equatorial archipelago, depend on effective global action to curb the drivers of anthropogenic climate change.